Model Interpretasi Alquran dalam Pendekatan Tafsir Kontekstual Abdullah Saeed - Thoriq Aziz Jayana (AL QUDS : Jurnal Studi Alquran dan Hadis, 2019)
This paper examines Abdullah Saeeds thought about the method of interpreting the Quran. While the method used in this paper is library research. In this paper, we will discuss from Saeed's thought which shows that he should consider his thinking in Islamic Studies, the initial basis for contextual interpretation, what principles must be held in interpreting the Koran, and more importantly the interpretation model offered by Saeed. In this paper we can summarize some points, that Saeeds thought as a refiner to Fazlur Rahmans hermeneutic double movement, seeks to provide an alternative in interpreting the Quran in the 21st century with a 'contextual interpretation' that is more flexible and takes into account the context of the revelation period, especially in ethically-charged verses legal. By calling himself a 'contextualist', Saeed formulated the steps of interpretation as a methodology that is interesting to study in the present, so that the Quran can still 'live' in all times; past, now and later.